ANALISIS POTENSI ANTIBIOTIKA BERDASARKAN KONSENTRASI HAMBAT MINIMAL DAN KONSENTRASI BAKTERISIDAL MINIMAL KLORAMFENIKOL DAN AMOKSISILIN TERHADAP SALMONELLA TYPHI - Deny Rudiansyah; Asep Dermawan; Yuliansyah Sundara Mulia (Poltekkes Kemenkes Bandung, 2021)
Infectious sicknesses are as yet one of the medical issues on the planet, including Indonesia. Different sorts of anti-toxins have been utilized to treat irresistible sicknesses. One illustration of an irresistible sickness brought about by microorganisms is typhoid fever or enteric fever brought about by Salmonella typhi (S.typhi.). Since 1948, chloramphenicol has been the medication of decision for S.typhi contamination. Objective: To think about and decide the anti-microbial power of chloramphenicol and amoxicillin against S.typhi. Exploration is expected to discover other anti-infection treatment alternatives that are more touchy. One of them is by directing this examination with the KHM and KBM tests. Methods: To see the potential for anti-microbials, the Minimum Inhibitory Concentration (MIC) was tried utilizing the cylinder weakening strategy and the Minimum Kill Concentration (KBM) utilizing the Kirby Bauer technique. This examination is a kind of in vitro lab test research. Information examination utilizing SPSS application with Mann Whitney U Test. Results: The examination showed that chloramphenicol had anti-infection power with a MIC worth of 12.50 g/ml, while amoxicillin had anti-infection potential with a MIC worth of 6.25 g/ml. The MBC an incentive for chloramphenicol and amoxicillin has a similar worth of 25 g/ml. Conclusion: There is no distinction in MIC and MBC esteems ​​between the anti-toxins chloramphenicol and amoxicillin against S.typhi. Amoxicillin can be utilized as an elective medication for the treatment of typhoid fever disease.